Proprioceptivna in senzorno-motorična vadba - Pšeničnik Sluga, Silvo (Šport (Ljubljana), 2023)
Postural balance is one of the most important abilities that enable older adults to move independently, efficiently, and safely. Proprioceptive training and sensorimotor training are frequently cited in the literature as effective approaches to improve balance and motor function in this population. At the same time, it is not entirely clear how the two training approaches differ and which of them is more effective. The results of our literature review show that proprioceptive and sensorimotor training have similar positive effects on balance in older adults. In particular, for dynamic balance, there were sig- nificant improvements in balance and, as a result, a reduction in the number of falls. Authors who defined training as proprioceptive reported improve- ments in static balance in all but two studies, while there was no improvement in stability during walking in one study. The authors defining training/ exercise as sensorimotor reached similar conclusions. Only two studies failed to find a statistically significant improvement in static balance (movement of the center of pressure on force plates), and one study found that there was improvement only in male subjects. Based on the training measures the authors used in their studies, we note that some the authors defined proprioceptive and sensorimotor training inconsistently. In addition, we found that in two studies, the authors defined the same training intervention once as proprioceptive and the second time as sensorimotor, although they are two different expressions or approaches.
Keywords: motorika; propriocepcija; ravnotežje; starejši ljudje; starostniki; šport